2020
DOI: 10.1016/j.ijscr.2020.08.048
|View full text |Cite
|
Sign up to set email alerts
|

A neglected case of chronic abdominal pain due to Lapsi seeds: A unique foreign body at unusual location

Abstract: Highlights Chronic partial jejunal obstruction leading to various non specific abdominal symptoms since 40 years. The first reported case of Lapsi seed stones causing partial jejunal obstruction. No change in morphological features of Lapsi seed stones when resided for long within human Gastrointestinal tract. First demonstration of radiological features of Lapsi seed stones both in vivo as well as in vitro. When patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…4,5 Various objects such as screws, drill bits, piercings, needles, bone fragments, seeds, and toothpicks have been reported to lodge in the appendix. 6,[9][10][11][12][13][14][15] Sharp and penetrating objects lodged in the appendix can cause perforation, while blunt objects may obstruct the lumen and lead to acute appendicitis with an inflammatory response. Occasionally, a foreign body may remain silent in the appendix without causing an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Various objects such as screws, drill bits, piercings, needles, bone fragments, seeds, and toothpicks have been reported to lodge in the appendix. 6,[9][10][11][12][13][14][15] Sharp and penetrating objects lodged in the appendix can cause perforation, while blunt objects may obstruct the lumen and lead to acute appendicitis with an inflammatory response. Occasionally, a foreign body may remain silent in the appendix without causing an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews reveals a variety of objects have been reported lodged in the appendix: bird shots, screws, drill bits, needles, bone fragments, seeds, and toothpicks [ [8] , [9] , [10] , [11] , [12] , [13] ]. It is theorized that the heavy weight of the metallic or radiopaque foreign body compared to gastrointestinal content causes its movement to be arrested in the cecum and the object gravitates toward the appendix due to its inferior anatomical position.…”
Section: Discussionmentioning
confidence: 99%